2022
DOI: 10.1161/jaha.121.022658
|View full text |Cite
|
Sign up to set email alerts
|

In‐Hospital Complications in Pregnancies Conceived by Assisted Reproductive Technology

Abstract: Background Assisted reproductive technology (ART) has emerged as a common treatment option for infertility, a problem that affects an estimated 48 million couples worldwide. Advancing maternal age with increasing prepregnancy cardiovascular risk factors, such as chronic hypertension, obesity, and diabetes, has raised concerns about pregnancy complications associated with ART. However, in‐hospital complications following pregnancies conceived by ART are poorly described. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This includes multifetal gestations, prematurity, cesarean delivery, placenta previa, abruptio placentae, preeclampsia, and gestational diabetes mellitus [ 11 ]. Subfertile females tend to have more pre-existing medical conditions, which increase the risk of maternal morbidity [ 4 , 12 ]. Obstetric hemorrhages have been reported to be increased after assisted reproduction technologies, but the mechanisms involved are unclear [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This includes multifetal gestations, prematurity, cesarean delivery, placenta previa, abruptio placentae, preeclampsia, and gestational diabetes mellitus [ 11 ]. Subfertile females tend to have more pre-existing medical conditions, which increase the risk of maternal morbidity [ 4 , 12 ]. Obstetric hemorrhages have been reported to be increased after assisted reproduction technologies, but the mechanisms involved are unclear [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al reported that the risk of adverse obstetric outcomes and vascular complications was higher in pregnancies conceived by ART compared to natural conception (17). Previous studies have suggested an increased risk of preterm delivery and IUGR in children conceived by ART (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Often these characteristics interact (older women are more likely to use ART, and have higher BMI), and therefore data may have significant confounding, highlighting the need to use randomised trials, ideally with stratification. Additionally, older women or those using fertility treatments are often excluded from trials as they are more likely to have complicated or multifetal pregnancies 47–49 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, older women or those using fertility treatments are often excluded from trials as they are more likely to have complicated or multifetal pregnancies. [47][48][49]…”
Section: Interpretation and Contextmentioning
confidence: 99%